The use of a prosthetic inlay resurfacing as a salvage procedure for a failed cartilage repair - Dhollander, Aad Alfons Maria; Almqvist, Karl Fredrik; Moens, Kris; Vandekerckhove, Pieter-Jan; Verdonk, René; Verdonk, Peter; Victor, Jan (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2015)
Purpose This study was designed to describe the clinical and radiographical outcome of the HemiCAP ® resurfacing system as a salvage treatment for a failed index cartilage procedure. Methods Fourteen patients were treated consecutively and clinically prospectively followed for a mean period of 26.1 ± 12.8 months. All patients were previously treated for their cartilage lesion. Radiographical data were analysed based on the Kellgren and Lawrence system. Results The patients involved in this study demonstrated a gradual clinical improvement in time. However, radiographically significant osteoarthritic changes were observed during the follow-up period. The position of the HemiCAP ® resurfacing system was adequate in all cases, and no signs of loosening were observed during the follow-up period. Conclusions The HemiCAP ® resurfacing system is feasible as a salvage treatment for a failed index cartilage procedure and resulted in a gradual clinical improvement. However, the favourable clinical outcome was not confirmed by the radiographical findings. Level of evidence IV.